Correlation between objective and subjective image quality measures of medical radiographs - Wan Hassan, Wan Muhamad Saridan; Munajat, Yusof; Sahibuddin, Shamsul (Faculty of Science, UTM, 2003)
Image quality of Lanex Regular/T Mat G and Lanex Regular/T Mat L screen-film systems was measured objectively by means of noise equivalent quanta (NEQ) and subjectively by means of receiver operating characteristic (ROC) curve analysis to study the correlation between the two measures. For the objective measure, uniformly exposed radiographs and radiographs of bar pattern test object were used to determine the NEQ. For the subjeclive measure, detection of simulated lesions in posteroanterior anthropomorphic chest radiographs by an observer was analysed by the ROC methodology. Both measures show that a low frequency signal shows better on Lanex Regular/T Mat L, whilst a high frequency signal shows better on Lanex Regular/T Mat G.